2018
DOI: 10.1371/journal.pone.0192938
|View full text |Cite
|
Sign up to set email alerts
|

Low-back electromyography (EMG) data-driven load classification for dynamic lifting tasks

Abstract: ObjectiveNumerous devices have been designed to support the back during lifting tasks. To improve the utility of such devices, this research explores the use of preparatory muscle activity to classify muscle loading and initiate appropriate device activation. The goal of this study was to determine the earliest time window that enabled accurate load classification during a dynamic lifting task.MethodsNine subjects performed thirty symmetrical lifts, split evenly across three weight conditions (no-weight, 10-lb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…sEMG will allow the detection of the early preparatory muscle activities to classify muscle loading and to initiate appropriate device activation. It has been shown that preparatory muscle activity can be leveraged to identify the intent to lift a weight up to 100 ms prior to load-onset [ 217 ]. The reduction of the effort will also be guaranteed by highly adaptive production processes.…”
Section: Discussionmentioning
confidence: 99%
“…sEMG will allow the detection of the early preparatory muscle activities to classify muscle loading and to initiate appropriate device activation. It has been shown that preparatory muscle activity can be leveraged to identify the intent to lift a weight up to 100 ms prior to load-onset [ 217 ]. The reduction of the effort will also be guaranteed by highly adaptive production processes.…”
Section: Discussionmentioning
confidence: 99%
“…Although loads were calculated using a biomechanical model, actual muscle activity generated in the shoulder muscles was not recorded. Our next step would explore using electromyography to obtain better results such as rate of fatigue (Totah et al, 2018). Moreover, objective measure such as time measurement could be used for comparing the performance between the tables.…”
Section: Discussionmentioning
confidence: 99%
“…Payload estimation and compensation could be achieved by exploiting classical inverse dynamics 16 or electromyography 17,18 , or a combination of the two. To achieve this, the exoskeleton needs to be equipped either with force/torque sensors or EMG electrodes, respectively, jeopardizing wearability, task-technology fit, and enduser willingness-to-use, already critical in the industrial context 19,20 .…”
Section: Related Work and Paper Contributionmentioning
confidence: 99%